Acute Myeloid Leukemia: Pattern of Clinical and Hematological Parameters in a Tertiary Care Centre - Khan, Muhammad Ihtesham (International Journal of Pathology, 2019)
Objective: To determine the pattern of clinical features, hematological parameters and subtypes of acute myeloid leukemia in our setup. Material and method: This Cross-Sectional Descriptive study was done in Khyber Teaching Hospital, Peshawar, from January 2015 to July 2017. All patients diagnosed as acute myeloid leukemia on bone marrow biopsy were included in the study. The demographics, clinical data and hematological parameters were noted on a proforma and results were drawn accordingly. Mean and standard deviation were used for quantitative data like age, while frequency and percentages were used for qualitative data like gender. Results: 41 cases were diagnosed as acute myeloid leukemia and were included in the study. Age of the study sample ranged from 3 years to 65 years, with mean of 41 ± 9.8 SD years. The commonest chief complaint was fever (51%), while the commonest sign was pallor (61%). There was decreased hemoglobin level and platelet count. M-2 was the commonest subtype seen in 24 (59%) cases. Conclusion: Acute myeloid leukemia occurs in younger age in our setup as compared to Western population. AML-M2 was the commonest subtype in AML. Fever and pallor were the commonest clinical findings while anemia and thrombocytopenia were the significant hematological findings.